Review on issues and challenges to sustainable urban development in the state of Uttarakhand - Avishek Ghosal; Anil Kumar; Sushil Kumar Rai (Renewable Energy and Sustainable Development)
State of Uttarakhand in India have gone through transitional change in the last decade. Urban population share have increased from ten percent to near about thirty percent of the total population. Due to this rapid urbanization the state of Uttarakhand, the state is finding difficult to attain sustainable development. Through this study we tried to identify the major challenges and issues which are blocking the urban areas of Uttarakhand from attaining sustainable development through a systematic review framework. The article attempts to highlight the issues and challenges which can be evaluated by researchers, academicians and policy makers in India and the world to study, evaluate and analyze the sustainable urban development of Uttarakhand. The methodology can also be used by researchers, academicians and policy makers to identify the challenges of sustainable urban development for any hill or mountain side terrain.   Received: 17 November 2023 Accepted: 12 April 2024 Published: 30 May 2024